2019
DOI: 10.1111/ggi.13765
|View full text |Cite
|
Sign up to set email alerts
|

Assessing hypoglycemia frequency using flash glucose monitoring in older Japanese patients with type 2 diabetes receiving oral hypoglycemic agents

Abstract: AimIt is important to consider hypoglycemia for glycemic control in elderly patients with type 2 diabetes. Continuous blood glucose monitoring system is an effective method to investigate blood glucose fluctuation. This study examined hypoglycemia frequency using continuous blood glucose monitoring system in older patients with type 2 diabetes.MethodsA total of 70 patients with type 2 diabetes aged >65 years, receiving oral treatment only and having a glycated hemoglobin (HbA1c) level of <8% were enrolled. Fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…4 -Forest plot for all included studies of fracture risk who treated with Sulfonylurea and those with Metformin. Hypoglycemia has been one of the many concerning side effects among patients receiving sulfonylurea [28]. Therefore, we speculate that hypoglycemia and increased risk of falls may be the cause of sulfonylureas-induced fractures.…”
Section: Discussionmentioning
confidence: 87%
“…4 -Forest plot for all included studies of fracture risk who treated with Sulfonylurea and those with Metformin. Hypoglycemia has been one of the many concerning side effects among patients receiving sulfonylurea [28]. Therefore, we speculate that hypoglycemia and increased risk of falls may be the cause of sulfonylureas-induced fractures.…”
Section: Discussionmentioning
confidence: 87%
“…50 A Japanese study has suggested sulfonylurea conversion when HbA1c < 6.3% or 6.7% in older diabetic patients. 51 Patients receiving glimepiride should be educated with regular monitoring of blood glucose and HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…23 The frequency of hypoglycemia in our study was concordant or even slightly higher than in previously published studies in older patients with T2D, including recent studies with CGM. 9,10,17,24 There are two potential explanations for this observation. First, the HYPOAGE population was older and under insulin therapy.…”
Section: Discussionmentioning
confidence: 99%